2011
DOI: 10.2478/10004-1254-62-2011-2073
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Lead in Croatian Wines by Graphite Furnace Atomic Absorption Spectrometry

Abstract: A method has been developed for direct determination of lead in wine by graphite furnace atomic absorption spectrometry (GFAAS) with Zeeman-effect background correction. The thermal behaviour of Pb during pyrolysis and atomisation stages was investigated without matrix modifi er and in the presence of Pd(NO 3 ) 2 , Pd(NO 3 ) 2 + Mg(NO 3 ) 2 x 6H 2 O, and NH 4 H 2 PO 4 + Mg(NO 3 ) 2 x 6H 2 O as matrix modifi ers. A simple 1:1 dilution of wine samples with Pd(NO 3 ) 2 as a matrix modifi er proved optimal for acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…During white winemaking, Pb is probably removed when grape skins and lead-attracting yeasts on the skins are eliminated prior to fermentation, which is not done in red wine vinification. In our recent research, we also found Pb concentration above the maximum permissible limit in a few homemade Croatian wines, whereas Pb concentration in commercially available Croatian wines was far below that limit [62]. Higher Pb concentrations are probably the result of infraction of technological norms, pollution from the container, smaller dilution, or mixture of different kinds of grapes.…”
Section: Metal Concentrations In Winementioning
confidence: 94%
“…During white winemaking, Pb is probably removed when grape skins and lead-attracting yeasts on the skins are eliminated prior to fermentation, which is not done in red wine vinification. In our recent research, we also found Pb concentration above the maximum permissible limit in a few homemade Croatian wines, whereas Pb concentration in commercially available Croatian wines was far below that limit [62]. Higher Pb concentrations are probably the result of infraction of technological norms, pollution from the container, smaller dilution, or mixture of different kinds of grapes.…”
Section: Metal Concentrations In Winementioning
confidence: 94%
“…Environmental lead exposure has dropped in recent decades thanks to the dominant use of unleaded petrol and the ban of lead-based paint and lead solder in food cans. The general population can be exposed to lead in food and drinks, including lead-contaminated folk remedies (30)(31)(32), drinking water (33), and wine (15)(16). Strongly acidic beverages (such as wine, fruit juices, and soft drinks) and food can be contaminated with lead if stored or served in leaded crystal glassware or lead-glazed ceramics.…”
Section: Sources Of Metal Exposurementioning
confidence: 99%
“…Cigarette smoke contains about 30 metals, of which cadmium, arsenic, and lead are in the highest concentrations, and cadmium body burden in smokers is about double that of non-smokers (14). Alcoholic beverages including wine can be contaminated with metals in concentrations exceeding the allowable limits and causing toxic effects, particularly in heavy drinkers (15)(16)(17).…”
mentioning
confidence: 99%
“…At present, there are many analysis methods for detection of heavy-metal ions, including atomic absorption spectrometry (ASS) (Porento et al 2011;Uluozlu et al 2010;Sanchez-Moreno et al 2010;Tariba, Pizent, and Kljakovia-Gaspic 2011), inductively coupled plasma atomic emission spectrometry (ICP-AES) (Boukraa et al 2006;Saracoglu et al 2006;Tokman and Akman 2004;Feist et al 2012;Sereshti et al 2012), inductively coupled plasma mass spectrometry (ICP-MS) (Zoorob, McKiernan, and Caruso 1998;Caruso et al 2003;Shih et al 2011;Trujillo et al 2012), high-performance liquid chromatography (Nolan and Lippard 2008;Liu, Lam, and Wong 2006), and enzymatic inhibition method (Hua and Lu 2003;Shyuan et al 2008;Ghica and Brett. 2008;Fragoso et al 2011;Chen et al 2011).…”
Section: Introductionmentioning
confidence: 97%